1995
DOI: 10.1146/annurev.med.46.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Borderline Hypothyroidism and Depression

Abstract: This review defines subclinical hypothyroidism and examines its influence on the occurrence and course of major depression. Recommendations are presented for the identification and treatment of patients with coexisting mood disorders and borderline thyroid failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
3
5

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(67 citation statements)
references
References 31 publications
2
57
3
5
Order By: Relevance
“…29, 45 Among the factors that predict response of lipid levels to levothyroxine therapy are higher levels of TSH, insulin resistance, higher levels of pretherapy cholesterol, and type III hyperlipidemia. Some evidence suggests that mild thyroid failure can aggravate bipolar disorder and depression 46 and that it is associated with abnormalities of muscle function, nerve conduction, cardiac function, 47 and cognitive and psychological function, with improvement after levothyroxine therapy. 45,[47][48][49][50] …”
Section: Serum Tsh Concentration Greater Than 10 Miu/lmentioning
confidence: 99%
“…29, 45 Among the factors that predict response of lipid levels to levothyroxine therapy are higher levels of TSH, insulin resistance, higher levels of pretherapy cholesterol, and type III hyperlipidemia. Some evidence suggests that mild thyroid failure can aggravate bipolar disorder and depression 46 and that it is associated with abnormalities of muscle function, nerve conduction, cardiac function, 47 and cognitive and psychological function, with improvement after levothyroxine therapy. 45,[47][48][49][50] …”
Section: Serum Tsh Concentration Greater Than 10 Miu/lmentioning
confidence: 99%
“…Furthermore, there is ample evidence to associate thyroid dysfunction with mood disorders. Indeed, one of the most obvious symptoms of overt hypothyroidism is affective disturbance, and abnormal thyroid activity, particularly subclinical hypothyroidism, is present in a disproportionately large number of patients with affective disorder (Haggerty and Prange 1995). Additionally, there is some evidence that depressed patients with either hypothyroidism and/or an antithyroid autoimmune response may be less responsive to antidepressant treatment.…”
Section: Do Thyroid Hormones Also Exert Neurotrophic Effects?mentioning
confidence: 99%
“…201 The clinical efficacy of adjunctive thyroxine (T4) or triiodothyronine (T3) in the treatment of refractory unipolar and bipolar mood disorders has been fairly well established. 202 Cole et al 203 observed in patients with bipolar depression that lower pretreatment thyroid activity (albeit within the normal range) predicted a worse response to treatment.…”
Section: Thyroid Hormone: Neurotrophic Effects In Critical Affective mentioning
confidence: 99%